Online Minimum-acceleration Trajectory Planning with the Kinematic Constraints - WANG Ying-Shi SUN Lei ZHOU Lu LIU Jing-Tai (自动化学报, 2014)
A novel approach based on a type of simplified motion planning （SMP） is presented in this paper to generate online trajectory for manipulator systems with multiple degrees of freedom （DOFs）. The key issue is to find minimum-acceleration trajectory planning （MATP） to optimize the arm motion to reduce disturbance. Moreover,necessary and sufficient conditions for solution＇s existence subject to all the kinematic constraints of joint position, velocity, acceleration and jerk are devised. Besides, this new method can be activated online from the arbitrary initial state to the arbitrary target state so that it enables the robot to change the original path at any time. Finally, the approach is applied to a real humanoid robot arm with seven DOFs to show its efficiency.